Analysis of Factors Affecting Performance - Amat Hasudungan Simanjuntak, Bastian; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This research is to look at the influence of motivation, work discipline, and job satisfaction on employee performance. The phenomenon that occurs at the BPJS Employment Pematang Siantar and Padang Sidimpuan Branch Offices is that the motivation given sometimes does not work for employees, it is only used as a formality for employees but is not carried out by employees, many employees are also undisciplined due to time problems and also work so that employee performance will not be optimal if employees do not comply with regulations, this occurs due to the employee's lack of satisfaction with the organization which does not pay attention to and improve the welfare of its employees so that employees prefer to work according to the standard and do not show their commitment to the organization. The results of this research are as follows: Work Discipline has a positive and significant effect on Employee Job Satisfaction with a value of 0.750 and a p value of 0.000 <0.05. Work Discipline has a positive and significant effect on Employee Performance with a value of 0.406 and a p value of 0.005 <0.005. Employee Job Satisfaction has a positive and significant effect on Employee Performance with a value of 0.361 and a p value of 0.011 <0.05. Motivation has a positive and significant effect on Employee Job Satisfaction with a value of 220 and a p value of 0.005. Motivation has a positive and significant effect on employee performance with a value of 0.210 and a p value of 0.016 <0.05. Work Discipline has a positive and significant indirect effect on Employee Performance through Employee Job Satisfaction with a value of 0.271 and a p value of 0.022. Motivation has a positive and significant indirect effect on employee performance through employee job satisfaction with a value of 0.079 and a p value of 0.038.